THE RELATIONSHIP BETWEEN LEARNING INTEREST AND LEARNING AREA IN THE HOME WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VII - Hasnawati Hasnawati; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The low interest in student learning can be seen from students paying less attention when math lessons are taking place. The noisy home situation makes it difficult for students to concentrate on learning mathematics at home. This study aims to determine the presence or absence of a positive and significant relationship between interest in learning and the learning environment at home with the learning outcomes of mathematics in students class VII MTs Muhammadiyah Gedongtengen Yogyakarta semester in the academic Year OfÂ  2017/2018. This study's population was all students of class VIII odd semester at State Junior High School (MTs) Muhammadiyah Gedongtengen Yogyakarta in 2017/2018, consisting of 2 classes. The sample was taken from class VII B, which consisted of 21 studentsâ€”the data collection ware test techniques and non - test. The data collection instruments were collected using a questionnaire and test methods. Test research instruments used were validity tests, different power tests, and reliability tests. The prerequisite test used was a normality test, linearity test, and independent test. Analysis of data used product-moment correlation analysis and multiple linear regression analysis. The results showed that there was a positive and significant relationship between interest in learning and the learning environment at home with the results of learning mathematics with Fcount = 5,3828 dan Ftable= 3,55 so that Fcount>Ftable, the double correlation coefficient ofÂ  (R) 0,6118 and the coefficient of determination doubleÂ  (R2) 0,3742. While the double regression equation Å¶ = 16,57 + 0,35 Xâ‚ + 0,42 Xâ‚‚ and obtained too RC = 40,15% and RC Â = 59,85% and EC = 15,03% and EC = 22,4%.